FROM DESCRIPTION CARD TOWARD E-PENGOLAHAN: PARADIGM CHANGE IN ARCHIVES DESCRIPTION: Array - 1 (Jurnal Kearsipan, 2021)
The background of this writing is so that the Indonesian people know that there has been a change in the process of describing static archives from using a description card to using an application. In this study, data collection techniques were used utilizing library research which has the aim of obtaining primary and secondary data so that it is expected to clarify various things found in the study. In addition, this research uses an archive research method called content study, which is a research methodology that utilizes a set of procedures to conclude the archives. In this study, an analytical method with content analysis techniques was used to understand this research. In the development of digital technology, there have been many paradigm shifts. One of the paradigm shifts is the change from static archive description cards to the use of E-Pengolahan applications.